THE FLUCTUATION OF CHLOROPHYLL-A CONCENTRATION DERIVED FROM SATELLITE IMAGERY AND CATCH OF OILY SARDINE (SARDINELLA LEMURU0)IN BALI STRAIT - J. LUMBAN GAOL; - WUDIANTO; - B. P. PASARIBU; - D. MANURUNG; - R. ENDRIANI (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2004)
The investigation is aimed to know the relationship between chlorophyll-a (chl-a) concentration and the abundance of Oily sardine (Sardinella lemuru), in Bali Strait. A time series of monthly mean chl-a data derived from Ocean Color Thermal Scanner (OCTS) sensor and Sea-viewing Wide Field-of View Sensor (SeaWiFS) during 1997-1999 are used in this study. Monthly Sardinella lemuru catch during 1997-1999 are obtained from fish landing data. The abundance of Sardinella lemuru is determined from acoustic data conducted in Bali Strait in September 1998 and May 1999. The result shows that the fluctuation of chlorophyll-a concentration in Bali Strait is influenced by monsoon and global climate change phenomena such as Dipole Mode (DM) event. During southeast Monsoon the upwelling process occurred around Bali Strait, so that the chl-a concentration is increased and during DM event occurred positive anomaly of chl-a concentration. The catch of Sardinella lemuru in Bali Strait is fluctuated during 1997-1999. The correlation between chl-a concentration and lemuru catch is positive and significant with certain time lag. Key words: Chlorophyll-a, Sardinella lemuru, Bali Strait, Satellite imagery